PENGGUNAAN MODEL PEMBELAJARAN GROUP INVESTIGATION (GI) TERHADAP KETERAMPILAN PROSES SAINS SISWA - Erfina Triutami; Darlen Sikumbang; Arwin Achmad (Universitas Lampung, 2014)
This study was aimed to determine the effect of media using Group Investigation (GI) model learning of Keterampilan Proses Sains (KPS). This study design was pretest-posttest non-equivalent group. Samples were VIIC and VIID, chosen by Purposive Sampling. Quantitative data of which obtained from the average value of test were analyzed by using t-test and U-test. The qualitative data which obtained from the observation sheet of learning activities and questionnaire responses of students were analyzed descriptively. The results showed that the use of GI learning model was able to improve KPS of student, it shown that the experimental class higher value of N-gain 66,38 and significantly different from the control class N-gain 51,43. Learning activities of the students also improve with average 72,30 of the experimental class and 50,23 of the control class. Most students gave positive respond to GI learning model. Penelitian ini bertujuan mengetahui pengaruh penggunaan model pembelajaran GI terhadap Keterampilan Proses Sains (KPS). Desain penelitian pretest-posttest kelompok non-equivalent. Sampel penelitian siswa kelas VIIC dan VIID, dipilih secara Purposive Sampling. Data penelitian berupa data kuantitatif yang diperoleh dari rata-rata nilai tes yang dianalisis menggunakan uji-t dan uji-U. Data kualitatif yang diperoleh dari lembar observasi aktivitas belajar dan angket tanggapan siswa yang dianalisis secara deskriptif. Hasil penelitian menunjukkan penggunaan model pembelajaran GI dapat meningkatkan KPS siswa, terlihat pada nilai N-gain 66,38 kelas eksperimen lebih tinggi dan berbeda nyata dibandingkan kelas control N-gain 51,43. Aktivitas belajar siswa juga meningkat dengan rata-rata 72,30 kelas eksperimen dan 50,23 pada kelas kontrol. Sebagian besar siswa memberikan tanggapan positif terhadap penggunaan model pembelajaran GI. Kata kunci : aktivitas siswa, keterampilan proses sains, model pembelajaran GI